2005
DOI: 10.1038/sj.ijo.0802908
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin: a relevant player in PPARγ-agonist-mediated improvements in hepatic insulin sensitivity?

Abstract: The potent insulin-sensitizing effects of peroxisome proliferator-activated receptor g (PPARg) agonists are well established. However, it is still a matter of intense debate as to which tissue(s) represent the most critical sites of action for PPARg agonists, and what the relevant target genes are that ultimately mediate the improvements in insulin sensitivity. The cell type with the highest levels of PPARg is the adipocyte, and as such the adipocyte is an excellent candidate cell to look for critical mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(105 citation statements)
references
References 49 publications
2
92
1
2
Order By: Relevance
“…We also examined whether fish oil might promote adiponectin secretion through activation of PPAR␥. Thiazolidinediones are synthetic ligands of PPAR␥ and have been shown to induce expression of the adiponectin gene and increase adiponectin levels both in vivo and in vitro (23)(24)(25). We found that acute and chronic fish oil treatment resulted in an approximately twofold increase in the expression of the adiponectin gene in epididymal fat, which was paralleled by an approximately two-to threefold increase in the expression of the PPAR␥-responsive gene CD36.…”
Section: Discussionmentioning
confidence: 56%
“…We also examined whether fish oil might promote adiponectin secretion through activation of PPAR␥. Thiazolidinediones are synthetic ligands of PPAR␥ and have been shown to induce expression of the adiponectin gene and increase adiponectin levels both in vivo and in vitro (23)(24)(25). We found that acute and chronic fish oil treatment resulted in an approximately twofold increase in the expression of the adiponectin gene in epididymal fat, which was paralleled by an approximately two-to threefold increase in the expression of the PPAR␥-responsive gene CD36.…”
Section: Discussionmentioning
confidence: 56%
“…HMW isoform may also be, as the major active form, preferentially utilized by liver or other target organs. 16,37 The study presents limitations that should be acknowledged. Quantification of the adiponectin isoforms was performed using semiquantitative WB method.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidizing environment within the lumen of endoplasmic reticulum favors disulfide bond formation through which trimers can further associate into middle-molecular weight (MMW) hexamers and high-molecular weight (HMW) multimers composed of 12 --18 monomers. 16,17 Mechanisms that regulate formation and distribution of adiponectin complexes in human AT and the contribution of different AT depots to circulating levels of particular isoforms are not known so far. The major biological effects of adiponectin in liver, muscle and endothelium have been attributed to HMW isoform of adiponectin.…”
Section: Introductionmentioning
confidence: 99%
“…31 Ablation of the ADN gene in mice results in insulin resistance, glucose intolerance, dyslipidemia and increased susceptibility to vascular injury and atherosclerosis. [32][33][34] Adiponectin reverses these abnormalities by stimulating oxidation of fatty acids, suppressing gluconeogenesis, inhibiting monocyte adhesion and inhibiting macrophage transformation, as well as proliferation and migration of smooth muscle cells in blood vessels. 17,32,35 In our study, we observed an improvement in both insulin resistance and adiponectinemia in losartan-treated patients.…”
Section: Correlationsmentioning
confidence: 99%